MID-TERM FORECAST FOR THE ICE CONDITIONS IN THE BERING SEA - A. N. Vrazhkin (Известия ТИНРО, 2020)
Application of CICE ice model for the mid-term (days) forecasting in the Bering Sea is considered, with short description of the model. Dependence of the sea surface temperature on the air temperature forecasted by GFS (Global Forecasting System) is determined. The ice concentration, ice cover, and the dates of ice formation are forecasted for the winter 2018/2019 using the model; its practical applicability is concluded.